Tribal economy : problems & prospects - Ramamani, V. S. (Allahabad, India : Chugh Publications, 1988)
Study conducted in Srikakulam District, Andhra Pradesh.
Revision of the author's thesis (Ph. D.--Andhra University, 1985)
Bibliography: p. [270]-279.
Robin
Keywords: Seethampeta Block (India) -- Scheduled tribes -- Economic conditions